Agonist triggering in oocyte donation programs—Mini review - Najdecki, Robert; Michos, Georgios; Peitsidis, Nikos; Timotheou, Evangelia; Chartomatsidou, Tatiana; Kakanis, Stelios; Chouliara, Foteini; Mamopoulos, Apostolos; Papanikolaou, Evangelos (Frontiers in Endocrinology, 2022)
Oocyte donation programs involve young and healthy women undergoing heavy ovarian stimulation protocols in order to yield good-quality oocytes for their respective recipient couples. These stimulation cycles were for many years beset by a serious and potentially lethal complication known as ovarian hyperstimulation syndrome (OHSS). The use of the short antagonist protocol not only is patient-friendly but also has halved the need for hospitalization due to OHSS sequelae. Moreover, the replacement of beta-human chorionic gonadotropin (b-hCG) with gonadotropin-releasing hormone agonist (GnRH-a) triggering has reduced OHSS occurrence significantly, almost eliminating its moderate to severe presentations. Despite differences in the dosage and type of GnRH-a used across different studies, a comparable number of mature oocytes retrieved, fertilization, blastulation, and pregnancy rates in egg recipients are seen when compared to hCG-triggered cycles. Nowadays, GnRH-a tend to be the triggering agents of choice in oocyte donation cycles, as they are effective and safe and reduce OHSS incidence. However, as GnRH-a triggering does not eliminate OHSS altogether, caution should be practiced in order to avoid unnecessary lengthy and heavy ovarian stimulation that could potentially compromise both the donor’s wellbeing and the treatment’s efficacy.